Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1999
DOI: 10.1126/science.284.5420.1677
|View full text |Cite
|
Sign up to set email alerts
|

The Fourth Dimension of Life: Fractal Geometry and Allometric Scaling of Organisms

Abstract: Fractal-like networks effectively endow life with an additional fourth spatial dimension. This is the origin of quarter-power scaling that is so pervasive in biology. Organisms have evolved hierarchical branching networks that terminate in size-invariant units, such as capillaries, leaves, mitochondria, and oxidase molecules. Natural selection has tended to maximize both metabolic capacity, by maximizing the scaling of exchange surface areas, and internal efficiency, by minimizing the scaling of transport dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

34
1,293
4
17

Year Published

2001
2001
2009
2009

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,478 publications
(1,348 citation statements)
references
References 2 publications
34
1,293
4
17
Order By: Relevance
“…In recent years, a body of theoretical work has become established, based on fractal geometry of O 2 supply networks, explaining why 0.75 would be expected to be the exponent for the scaling of metabolic rate. 17 But this work largely ignores the fact that exponents of 0.75 have never been an established feature of the empirical database. Indeed, more recent empirical work has established that, once phylogenetic effects are accounted for (in other words, effects due to a shared evolutionary origin), the most parsimonious exponent is strongly dependent on the group being studied, [18][19][20] and there is no uniform scaling exponent -be it 0.66 or 0.75 -for either basal or maximal metabolic rate.…”
Section: Comparison Of Energy Expenditure In Lean and Obese Animalsmentioning
confidence: 99%
“…In recent years, a body of theoretical work has become established, based on fractal geometry of O 2 supply networks, explaining why 0.75 would be expected to be the exponent for the scaling of metabolic rate. 17 But this work largely ignores the fact that exponents of 0.75 have never been an established feature of the empirical database. Indeed, more recent empirical work has established that, once phylogenetic effects are accounted for (in other words, effects due to a shared evolutionary origin), the most parsimonious exponent is strongly dependent on the group being studied, [18][19][20] and there is no uniform scaling exponent -be it 0.66 or 0.75 -for either basal or maximal metabolic rate.…”
Section: Comparison Of Energy Expenditure In Lean and Obese Animalsmentioning
confidence: 99%
“…A third alternative was proposed with the "West-Brown-Enquist Law" with ⌬ between 2.0 and 3.0, depending on bifurcation level. This variant additionally assumed "fractal-like" ramification patterns and made interesting predictions about the scaling properties (i.e., body size dependency) of vascular systems in various species (West et al, 1997(West et al, , 1999.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the model does not make a priori assumptions about a "fractal" geometry (West et al, 1997(West et al, , 1999 but still can lead to apparently self-similar bifurcation patterns in some regions, which correspond closely to the vascular patterns in real, rapidly growing, and remodeling networks . We wish to emphasize that statements such as "blood vessels are fractals" fail to address properly both the underlying mathematics for generating fractals and for measurement of a fractal dimension (Kurz, 2000;Sandau and Kurz, 1997).…”
Section: Hemodynamics and Biomass Distributionmentioning
confidence: 99%
“…We wish to emphasize that statements such as "blood vessels are fractals" fail to address properly both the underlying mathematics for generating fractals and for measurement of a fractal dimension (Kurz, 2000;Sandau and Kurz, 1997). Notably, fundamental aspects of transport networks have been referred to as merely "fractal-like" (West et al, 1999) and, as we proposed earlier (Kurz and Sandau, 1998), it has been shown that fractal geometry is not necessary for the observed scaling relations across animal species (Banavar et al, 1999). Although the issue of "fractal ge- ometry" is a matter of ongoing debate, we believe that a detailed analysis of biophysics, including transport of oxygen and metabolites, should always be aware of "nonfractal" topographical restrictions and morphologic heterogeneity present in vascular systems.…”
Section: Hemodynamics and Biomass Distributionmentioning
confidence: 99%
See 1 more Smart Citation